PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL DIRECT INSTRUCTION DAN MODEL INKUIRI PADA MATA PELAJARAN IPA KELAS V SDN 101816 PANCUR BATU TAHUN PEMBELAJARAN 2018/2019 - KEMBAREN, ANGELIA KEKE BEGITA (Jurnal Ilmiah Aquinas, 2019)
This Research aims to find out the differences of direct instruction model and inquiry model in improving learning outcomes of the fifth grade students on science subject with material objects and properties of objects at SDN 101816 Pancur Batu in academic year 2018/2019. The number of students population at SDN 101816 Pancur Batu in academic year 2018/2019 are 534 students. This sample taken by sampling purposive 66 students. The model used in the study is an experimental model is one-group pretest-posttest design.The model in this study uses experiments conducted in two groups, namely experiment I and experiment II. The instrument used to capture data is multiple choice tests in material objects and their properties.Based on statistical data processing in group I obtained the average results that is 73.23, standard deviation 6,85 and standard error 1.19 out of 34 students. For the experimental group II, the average results were 86.56, standard deviation was 6.55 and the standard error was 1.17 from the total 32 students. By using the "t" test, it was obtained to = 7.949 and then consulted with the table that is dk = 66 at a significant level of 5% = 1.99. Therefore, the obtained to be greater than t table is 7,949 the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. This proves that the Inquiry model is better than the Direct Instruction model of material objects and their properties. Therefore, it can be concluded that the Inquiry model is more effective than the Direct Instruction model of material objects and their properties the fifth grade students of SDN 101816 Pancur Batu academic year 2018/2019.